Alternative sentencing of parent offenders and implications on the rights of the child in Uganda's criminal justice system - Akonumbo, Atangcho Nji (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2008.